Neurological and mental health in the era of climate change: mechanisms, clinical impacts, and adaptation - Martínez Lozada, Pablo S.; Leon-Rojas, Jose E. (Frontiers in Public Health, 2025)
Climate change has become a global health emergency in recent decades, with far-reaching effects on neurological and psychiatric health; however, their relationship remains poorly understood. Climate-related phenomena impact neurological and mental health through both direct and indirect mechanisms, including progressive temperature changes and more frequent extreme weather events. This has influenced the prevalence and geographic distribution of neurological disorders, affecting the public health landscape of these diseases. The primary mechanisms include thermal stress, neuroinflammation due to air pollution, ecological shifts that increase exposure to neurotropic infections, psychological stress, and disruptions to healthcare systems. These factors interact and amplify the risk of neurological diseases, including neurodegenerative, neuroinflammatory, cerebrovascular, neuroinfectious, and psychiatric conditions. The aim of this study was to synthesize evidence from peer-reviewed studies in major databases on the impact of climate change–related factors in the incidence, severity, and distribution of neurological and psychiatric disorders. Addressing the effect of climate change on these diseases requires improved healthcare strategies, scientific research, and climate change mitigation to protect brain health and reduce neurological disease burden.